2022
DOI: 10.3389/fcvm.2021.802566
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Antiplatelet Medication in COVID-19-Related Thrombotic Complications

Abstract: Coronavirus disease 2019 (COVID-19) induces a hypercoagulatory state that frequently leads to thromboembolic complications. Whereas anticoagulation is associated with reduced mortality, the role of antiplatelet therapy in COVID-19 is less clear. We retrospectively analyzed the effect of anticoagulation and antiplatelet therapy in 578 hospitalized patients with COVID-19 and prospectively monitored 110 patients for circulating microthrombi and plasma markers of coagulation in the first week of admission. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To determine if the circulating platelets of patients with COVID-19 could form pathological platelet–platelet aggregates in vivo, we quantified directly in whole blood the CD41a+ events that were larger than regular platelets but did not bind leukocytes, previously described as circulating microthrombi [ 15 , 16 ]. Platelet–platelet aggregates were detected in the blood of unvaccinated COVID-19, most frequently in patients admitted to the ICU, but not in vaccinated patients with COVID-19 (fold change non-ICU: 2.3 ± 2.6; ICU: 3.5 ± 4.1; vaccinated: 0.9 ± 1.0) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the circulating platelets of patients with COVID-19 could form pathological platelet–platelet aggregates in vivo, we quantified directly in whole blood the CD41a+ events that were larger than regular platelets but did not bind leukocytes, previously described as circulating microthrombi [ 15 , 16 ]. Platelet–platelet aggregates were detected in the blood of unvaccinated COVID-19, most frequently in patients admitted to the ICU, but not in vaccinated patients with COVID-19 (fold change non-ICU: 2.3 ± 2.6; ICU: 3.5 ± 4.1; vaccinated: 0.9 ± 1.0) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…As for the controversies about the efficacy of antiplatelet drugs, different conclusions may be drawn based on the bias in clinical trials, such as patients with different disease severity, the phase and duration of drug use, combinations of other drugs, diverse primary outcomes, and so on ( Table 1 ). Analysis of a retrospective study showed no association of antiplatelet therapy (aspirin and/or P2Y 12 receptor antagonists) with survival in hospitalized patients with COVID-19 ( 119 ). In a randomized controlled study, in-hospital antiplatelet therapy was less likely to improve organ support-free days within 21 days in critically ill patients, but it improved the probability of survival to discharge (97%) and survival over 90 days (99.7%) ( 120 ).…”
Section: Treatmentmentioning
confidence: 98%
“…COVID-19 induced hypercoagulatory state that frequently leads to thromboembolic complications, whereas anticoagulation is associated with reduced mortality and role of anti-platelet therapy is very less clear [17]. It is very evident that anti-platelet therapy might be effective in improving the ventilation in COVID-19 patients with severe respiratory failure.…”
Section: Role Of Anti-platelet Therapymentioning
confidence: 99%
“…The hypercoagulatory state induced in COVID-19 shows clinical and laboratory features with partially overlapped bacterial sepsis induced coagulopathy (SIC) but represents a unique condition that has been termed "COVID Associated Coagulopathy" (CAC) [24] which is characterized by wide spread deregulation coagulation parameters such as D-dimer, prolonged prothrombin time and slight reduction in platelet count [25]. The precise mechanism of COVID Associated Coagulopathy (CAC) is under investigation and seems very complexed due to several patho-physiological environmental conditions created by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection which is influenced by plethora of mediators [17]. Immunothrombosis represents crucial link with hypercoagulability, endothelial dysfunction, severe respiratory failure wherein neutrophils, platelets are dysregulated in coagulation cascade work [26][27][28].…”
Section: Role Of Anti-platelet Therapymentioning
confidence: 99%